PENGARUH POPULASI TANAMAN DAN PENGGUNAAN MULSA TERHADAP POPULASI GULMA DAN HASIL PUCIL JAGUNG MANIS (ZEA MAYS SACCHARATA STURT) DI LAHAN KERING - I Ketut Arsa Wijaya (AGRICA, 2013)
This study was conducted in Balai Benih Induk (BBI) Luwus, Baturiti District, Tabanan Regency, with the high of place 506m above sea level occurring in March to May 2014. This research used randomized block design arranged per factor, namely population of plants (P) including three steps: P1=80.000 plants per hectare, P2= 100.00 plants per hectare, P3= 120.000 per hectare; and mulch (M) that include: M0= without mulch and without cleaning, M1= without mulch with clean weeding, M2= rice plants straw mulch (5 ton per hectare) and M3= black silver plastic mulch. Eventually, there were 12 combination treatments, each of which was repeated 3 times to obtain 36 land slots. The research indicates that there was no real interaction between the treatment of plant population and mulch usage in all variables observed. The 100.000 plant population per hectare can produce the weight of dry and fresh oven corn kernel without highest cornhusk that was to say 4.79 tons and 0.53 tons or 11.66 % and 20.45% higher compared to 120.000 plant population per hectare. The use of black silver plastic and rice plants straw mulch can produce the weight of fresh and dry oven corn kernel without cornhusk per hectare each of which is 4.69 tons, 4.57 tons, and 0.54 tons, 0.47 tons or 26.76%, 38.46 %, and 23.51 %, 20.51 % higher than without mulch and without clean weeding. Clean weeding treatment can produce the weight of fresh and dry oven corn kernel without cornhusk per hectare with its weight of 4.63 tons and 0.51 tons or 25.35 % and 35.90 % higher than without mulch and cleaning. Clean weeding treatment was not obviously different from mulch treatment. The identification of weed types were 19 kinds of weeds and Cyperus rotundus L. Weeds. They have the highest density and each absolute frequent of 1249.333 stems m-2 and 1.00.